Leadership style in the Covid-19 pandemic situation in Indonesian villages - Anta Ibnul Falah (Badan Penelitian dan Pengembangan Provinsi Sumatera Utara, 2022)
In pandemic situations with social restrictions, the society, especially marginal communities with micro and informal businesses, is believed to be the most socio-economically vulnerable. However, the presence of effective leadership can help these communities to deal better with pandemic risks. As indicated in the Gini Ratio, during the pandemic, the leadership role in villages looks more prosperous than in cities. Therefore, this study intends to describe these villages' leadership roles and assess the relevant leadership styles practiced. This research is qualitative research conducted with a Systematic Literature Review (SLR) approach to the results of previous research in Indonesian villages, considering that there has been no similar research conducted before. The results of this study indicate that the vital role of villages leaders in a pandemic situation is seen for example in fullfiling citizen's basic needs, strengthening village food security, maintaining environmental security, providing moral support/social assistance and education, allocating and mobilizing aid on target, as well as supporting governmental policies. The most prominent leadership styles in supporting villages' success during pandemic situations are collaborative, transformational, and a combination of collaborative-transformational leadership styles. And the most important capabilities are motivating, guiding, educating, role-modeling, learner, inclusion, embracing, and supporting. These leadership styles and capabilities are expected to be relevant in all Indonesian villages, noticing that previous studies included are quite scattered from Java, Sulawesi, Sumatra, Nusa Tenggara, and Kalimantan, even though there are no research representatives from the easternmost of Indonesia, such as Maluku and Papua.